PERBANDINGAN TEKNIS DAN EKONOMIS ANTARA PENGGANTIAN BANTALAN POROS PROPELLER DIBANDINGKAN DENGAN PENGGESERAN POSISI V-BRACKET PADA KMP. KUMALA - Budiarto, Untung (TEKNIK, 2010)
In the propulsion systems there are three preference components main engine, propeller shaft, and propeller.KMP. Kumala is one for all passengers ship the owner PT. Darma Lautan Utama, there are it’s to experienceproblems to the systems propulsion to happen missalignment between construction v-bracket with sterntube,there are v-bracket to function become to hold up propeller shaft in the inside to find shaft bearing. Effect themissalignment, shaft can’t to turn, so need the realized preparing with the change to shaft bearing shapeexentric and to scrape position v-bracket the position again. In this finish task purporting to know the valuefrom side technics and economics between to realized the change shaft bearing shape exentric with to scrapeposition v-bracket to position again with account time to docking next time. From the result analyse to find thatto change the shaft bearing shape exentric to need faster time, material cost is more expensive, labour cost ischeaper, construction to v-bracket isn’t normaly, than to scrape position v-bracket to need the time is long time,material cost is cheaper, job cost is more expensive, construction v-bracket back to normal the position again,until to moment realization docking next time to need faster time, material cost and job cost is cheaper from tochange the shaft bearing shape exentric.